2021
DOI: 10.1186/s13018-020-02188-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of postoperative effectiveness of less invasive short external rotator sparing approach versus standard posterior approach for total hip arthroplasty

Abstract: Background Most of the studies assessing the corrective posterior total hip arthroplasty (THA) mainly focused on the mini-incision approach. Studies exploring the short external rotator sparing approach are rare. Therefore, this study aimed to compare the effectiveness of standard posterior approach and short external rotator sparing approach. Methods This prospective observational study included 126 patients who underwent THA in June 2017–June 201… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The CPP approach was shown to be consistently favored and superior in gaining ability to walk postoperatively. Previous studies have reported an average postoperative hospital stay of around 1 week, regardless of whether MIS-THA or conventional THA, anterior or posterior approach was used [7,18,20,27,28]. One of the reasons for the longer postoperative hospital stay in this study was that participants needed to live alone without anyone support after discharge.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The CPP approach was shown to be consistently favored and superior in gaining ability to walk postoperatively. Previous studies have reported an average postoperative hospital stay of around 1 week, regardless of whether MIS-THA or conventional THA, anterior or posterior approach was used [7,18,20,27,28]. One of the reasons for the longer postoperative hospital stay in this study was that participants needed to live alone without anyone support after discharge.…”
Section: Discussionmentioning
confidence: 81%
“…However, studies comparing postoperative function between THA with MIS techniques and conventional techniques have been inconsistent in their conclusions, with some reporting signi cant improvement with MIS-THA, others reporting a limited advantage, and others nding no signi cant difference between MIS-THA and conventional THA. [18][19][20][21][22][23]. The conjoined tendon-preserving posterior (CPP) approach is also a minimally invasive posterior approach that preserves short external rotator muscles, except for the quadratus femoris and obturator externus muscles, and the posterior and anterior capsular ligaments without cutting them [24].…”
Section: Introductionmentioning
confidence: 99%